Safe, Autonomous and Intelligent Vehicles - Yu, Huafeng; Li, Xin; Murray, Richard M.; Ramesh, S.; Tomlin, Claire J. (Unmanned System Technologies, 2019)
This book covers the start-of-the-art research and development for the emerging area of autonomous and intelligent systems. In particular, the authors emphasize design and validation methodologies to address the grand challenges related to safety. This book offers a holistic view of a broad range of technical aspects (including perception, localization and navigation, motion control, etc.) and application domains (including automobile, aerospace, etc.), presents major challenges and discusses possible solutions. Provides a single-source guide to the practical challenges in designing autonomous and intelligent systems; Discusses the major challenges related to safety of next-generation autonomous and intelligent systems, given growing complexity and new applications; Describes new design and validation methodologies to address safety issues; Includes technical background to facilitate further research and development.